2017 IEEE Applied Power Electronics Conference and Exposition (APEC) 2017
DOI: 10.1109/apec.2017.7930691
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and reliable DC-DC converter for smart transformer

Abstract: Abstract-The series-resonant converter (SRC) has been used in several application and it recently became popular for Smart Transformers (STs). In this application, the efficiency and reliability are of paramount importance. Although many papers have addressed the design challenges to improve the converter efficiency, discussions about the reliability are still missing in literature. In this context, this paper presents a design procedure focusing on the efficiency and reliability improvement of the SRC for ST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…On the other hand, the new technology of Silicon-Carbide MOSFETs has emerged as a high performance and economically viable solution. These devices have been used to implement the power converters of the ST architecture in [11], [12]. However, the potential of such semiconductors is still an open question in the power electronic field.…”
Section: B Semiconductor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the new technology of Silicon-Carbide MOSFETs has emerged as a high performance and economically viable solution. These devices have been used to implement the power converters of the ST architecture in [11], [12]. However, the potential of such semiconductors is still an open question in the power electronic field.…”
Section: B Semiconductor Analysismentioning
confidence: 99%
“…The weight of copper used is determined using the volume and the copper density d cu = 8.96g/cm 3 W cu = v cu d cu (10) Then, replacing (8) in (10), the total amount of copper required is given by (11). Note that the required copper is proportional to the power processed by the winding.…”
Section: Appendix B -Price Estimation Of the Magnetic Componentsmentioning
confidence: 99%
“…1. This converter was employed in ST application in [16], focusing on the comparison of different modulation strategies. This study has shown that the QAB converter presents higher performance when the Phase Shift Modulation (PSM) scheme is used.…”
Section: Modular Smart Transformer Architecturementioning
confidence: 99%
“…This study has shown that the QAB converter presents higher performance when the Phase Shift Modulation (PSM) scheme is used. On the other hand, only an initial studies was presented in [16], without substantial results. In this context, the current work focus on the optimum multi-objective design of the QAB converter, with the aim to maximize efficiency and minimize cost.…”
Section: Modular Smart Transformer Architecturementioning
confidence: 99%
“…Conversores CC-CC ressonantes (CR) são estruturas com aplicações em importantes áreas da eletrônica de potência, como alta tensão [1]- [6], veículos elétricos [7], fontes renováveis [8], [9], transformadores eletrônicos [10], [11], fontes de alimentação de baixa tensão [12], entre outras aplicações [13], [14]. Os conversores ressonantes se caracterizam por aproveitarem os elementos parasitas dos componentes do conversor, utilizando-os em suas etapas de operação e para realizar comutação suave, o que pode contribuir na obtenção de alta eficiência e eliminação de problemas de interferência eletromagnética.…”
Section: Introductionunclassified